Effects of Water Clover Density and Submerged NPK Fertilizer on Rice Production - Budiastuti, Maria Theresia Sri; Supriyono, Supriyono; Rahayu, Muji; Setyaningrum, Desy; Septin, Latiffah Indriana (PLANTA TROPIKA, 2024)
Water clover is an important weed that causes a decrease in rice yields by 15-42%. This study examined the effects of water clover density andNPK fertilizer application on rice yields. This study was arranged in a complete randomized block design with two factors. The first factor was water clover density with three levels, consisting of no water clover, one water clover, and two water clover. The second factor was the application of NPK, which was applied to the surface, submerged in 3, 6, and 9 cm—performed with three replications. Water clover density affected the number of rice panicles, the number of rice grains per panicle, the weight of 100 seeds, rice biomass, and water clover biomass. The application of submerged NPK affected rice biomass. The application of NPK on the surface reduced the highest rice biomass. Two water clovers per rice plant reduced the number of rice panicles by 39% compared to without weeds. Rice biomass decreased by 40% and 50% at weed density of one and two water clover weeds per rice plant, respectively. The higher the density of clover weeds, the higher the decline in harvest yields and the higher the biomass of clover weeds.